Aktivitas Finger Painting untuk Meningkatkan Kemampuan Konsentrasi Anak ADHD (Attention Deficit Hyperactivity Disorder) - Novi Cynthia Yusnita; Afdhalina Afdhalina (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2026)
Children with Attention Deficit Hyperactivity Disorder (ADHD) generally experience difficulties in focusing their attention, maintaining concentration, and following instructions during the learning process. As this condition can impact both academic and social development, there is a need for engaging instructional strategies tailored to their specific characteristics. This study aims to describe the implementation of finger-painting activities and illustrate their role in enhancing the concentration skills of children with ADHD. A qualitative, descriptive research approach was employed. The study subjects comprising a child with ADHD, a classroom teacher, and the child's parent were selected using purposive sampling. Data were collected through observation, semi-structured interviews, and documentation. The findings indicate that finger painting activities can increase attention span and student engagement in learning tasks, while also helping to reduce distractible behavior. Furthermore, the activity provides enjoyable sensory stimulation, making it easier to guide the child to remain focused.